Distributed selection and fusion of translation tools - ZHENG LIHUA (2019)
The invention provides a distributed selection and fusion method of translation tools, a computer system and a computer readable medium, which can realize reasonable selection of corresponding translation tools according to the distribution condition of a to-be-translated text in a translation process and realize the fusion of different translation tools. The computer system comprises a subject term determination subsystem, a distribution map generation subsystem and a translation tool fusion system; the computer system further comprises a distribution map-translation tool corresponding database which is used for storing the translation tools corresponding to different distribution maps. 本发明提出了种翻译工具的分布式选择与融合方法、计算机系统与计算机可读介质，可以实现在翻译过程中根据待译文本的分布情况，合理选择相应的翻译工具，并实现不同翻译工具的融合。所述计算机系统包括主题词确定子系统、分布图生成子系统、翻译工具融合系统；所述计算机系统还包括分布图-翻译工具对应数据库，用于存储不同分布图对应的翻译工具。